Pengaruh Pembelajaran Pendidikan Agama Islam Terhadap Karakter Religius Siswa - Siti Hasbiatun; Mujib; Imam Syafe'i (PAI RAFAH, 2024)
In shaping one's behavior, to be able to distinguish and determine whether something is good or bad, religious values are used as guidelines. Education is one of the influential platforms in the formation of religious values. Through learning Islamic religious education, it is hoped that students can understand and carry out good habits so that they have a religious character. This study uses quantitative methods and sampling using non-probability sampling techniques, namely purposive sampling. From the results of the Islamic religious education hypothesis test using Multiple Linear Regression, which shows a significance level <0.05, which means that the hypothesis in this study rejects H0 and accepts Ha. So it can be said that “Islamic Religious Education Learning has a Significant Effect on the Religious Character of Students at SMP Negeri 1 Bandar Lampung, SMP Negeri 5 Bandar Lampung, SMP Negeri 21 Bandar Lampung and SMP Negeri 36 Bandar Lampung.